PENGEMBANGAN BAHAN AJAR BERBANTUAN SOFTWARE MATLAB PADA MATERI MATRIKS KELAS XI SMA - Rosliana; Andi Halimah; Andi Dian Angriani (Universitas Islam Negeri Alauddin Makassar, 2022)
This research explains the development of Matlab Software based teaching material for teaching matrix in the 11th grade of Senior High School. The purposes of this research are (1) to develop Matlab Software-based teaching material for the teaching matrix; (2) to evaluate the level of the validity, the practices, and the effectiveness of Matlab Software-based teaching material for the teaching matrix. Research and development were used in conducting this study by applying the ADDIE model which stands for Analysis, Design, Development, Implementation, and Evaluation. The developed product was in form of a Mathematics module consisting of the matrix lessons completed by the syntax of Matlab Software. The subject involved in this research was the students of XI MIPA 2 in SMA Negeri 6 Makassar. In addition, the researcher used the validation expert sheets, observation sheets, questionnaires, and tests. The procedure of this research started from the analysis phase until the evaluation step as the whole process included as ADDIE model. Based on the result of the tryout, it could be concluded that (1) the module was categorized in the level of high validity considering its position on the  interval; (2) the product was practical since the whole aspect was completely done; (3) the module was effective considering the level of completeness reached 100%. Thus, the students' comprehension test was totally completed. Meanwhile, the result of observation of students' activity using Matlab Software was also very good. Therefore, the conclusion is that the development of Matlab Software-based teaching material for the teaching matrix in the 11th grade of Senior High School has achieved the criteria of validity, practicality, and effectiveness.